Perancangan Mesin Pencacah Limbah Kelapa Muda Secara Vertikal Menggunakan Metode Sintesis Pandangan - Robert Napitupulu, S.ST., M.T.; Yuli Dharta; Diviya Arsieka Putri; Devaned Parlindungan; Aldi Pratama; Clara Lavita Angelina (Jurnal Teknologi, 2023)
Increasing consumption of young coconuts (known as "Kelamud") is leading to a rise in the amount of waste generated by these coconuts. A group is using this waste as a raw material for the production of compost fertilizer for oil palm trees. However, the process is still performed manually by chopping waste with a machete of 15-20 mm thickness, which takes a considerable amount of time. This research aims to design and construct a machine for vertically chopping coconut waste. The proposed research method is a synthesis strategy that combines design concepts with the steps of clarifying and translating the client's desires. Then, these desires are incorporated into the machine design procedure by making selections, analyzing the interdependence and interrelationships between the selections, assessing trade-offs, and evaluating the outcomes of these selections. The final design of the Kelamud chopper machine consists of a motor with a 5.5 horsepower gasoline engine, a chopping system with a four-blade knife system, and a transmission system with pulleys and belts. Based on the results of the tests, the machine is capable of chopping waste from young coconuts with a capacity of 232.62 kg/hour in fibrous properties.